PENGARUH PENDIDIKAN TERAKHIR, SKALA USAHA DAN PELATIHAN AKUNTANSI TERHADAP PENGGUNAAN INFORMASI AKUNTANSI PADA UKM. (STUDI EMPIRIS TERHADAP UKM DI DESA KEDENSARI, KECAMATAN TANGGULANGIN KABUPATEN SIDOARJO) - Zulkarnnaeni, Achmad Syahfrudin; Rizki, Novitasari Caesar (Jurnal Ilmiah Akuntansi Indonesia, 2019)
This study aims to determine the effect of recent education, business scale and accounting training of the use of accounting information in SMEs ?. (Empirical study of SMEs in Kedensari Village, Tanggulangin District, Sidoarjo Regency). The research approach used in this research in quantitive research. The population in this study were all handicraft industries in Kedensari Village, Tanggulangin District, totaling 42 SMEs. Based on the census methode, the number of samples in this study were all handicraft industries in Kedensari Village, Tanggulangin District, amountingto 42 entrerpreneurs. The methode of collecting data through a questionnaire methode, which is to spread the list of questions (questionnaire) that will be answered by respondents, namely SME bussines owner licatied in Kedensari Village, Tanggulangin District, Sidoarjo Regency. The result showed that namely: (1) Latest Education influences the Use of Accounting Information in SMEs; (2) Business Scale influence the Use? of Accounting Information in SMEs; and (3) Accounting Training influences the Use of Accounting Information in SMEs. Keywords:?????? Education, Business Scale, Accounting Training and Use of Accounting Information